ELECTRONIC EDUCATION IN UNDERGRADUATE RADIOLOGY: THE EXPERIENCE OF THE UNIVERSITY OF MALAGA - Francisco Sendra Portero (Ediciones Universidad de Salamanca, 2010)
Since 1998, radiology teaching and learning electronic resources have been developed at the University of Málaga. Some experiences on undergraduate radiology education are presented in this paper: a self-conducted training on radiology called "A Walk through Radiology", some projects to create and develop radiology consulting tools, a project about audio-recorded virtual lectures (AMERAM), started on 2005, and a Web portal to collect radiology education Internet resources. Finally, we conclude with some reflections about the experience along these years, which has contributed to improve the student's radiology learning in our centre and has supplied educative tools to students and postgraduates of this and other cities. We consider that the European Space of Higher Education learning philosophy, student centered and self-learning based, gives a vital role to undergraduate electronic education tools.